2019
DOI: 10.1111/and.13275
|View full text |Cite
|
Sign up to set email alerts
|

14‐3‐3 epsilon plays an important role in testicular germ cell apoptosis: A functional proteomic study of experimental varicocele

Abstract: The latest perspective indicates that apoptotic dysregulation is an important mechanism in male infertility induced by varicocele. To elucidate the molecular mechanism of apoptosis caused by varicocele, we used proteomics (2D-MALDI-TOF MS) to identify the altered proteins in the testes of experimental varicocele rats compared with the control. Here, 21 significantly different protein spots were detected by proteomics technology. 14-3-3 epsilon (14-3-3ε) was our subsequent research target because of its functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Their roles in spermatogenesis, normal sperm function, and male fertility have been reported in mice. Such observations imply that dysregulation in proteins involved in apoptotic mechanisms may lead to infertility . Two chaperonin-related protein-coded genes, CCT7 and CCT2, were overexpressed in COVID-19-recovered patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their roles in spermatogenesis, normal sperm function, and male fertility have been reported in mice. Such observations imply that dysregulation in proteins involved in apoptotic mechanisms may lead to infertility . Two chaperonin-related protein-coded genes, CCT7 and CCT2, were overexpressed in COVID-19-recovered patients.…”
Section: Discussionmentioning
confidence: 99%
“…Such observations imply that dysregulation in proteins involved in apoptotic mechanisms may lead to infertility. 39 Two chaperonin-related protein-coded genes, CCT7 and CCT2, were overexpressed in COVID-19-recovered patients. These are the vital subunit proteins of the molecular chaperone complex CCT/TRiC (chaperonin containing the T-complex/TCP1-ring complex) present in haploid germ cells.…”
Section: Acsmentioning
confidence: 98%
“…45 More studies have found that members of the Bcl-2 protein family play an important role in 14-3-3-mediated cell proliferation and apoptosis. [46][47][48] As one of the pro-apoptotic proteins of the Bcl-2 family, BAD is phosphorylated by Akt, and 14-3-3 then binds to the phosphorylated BAD to induce conformational changes in BAD and promote the separation of BAD from Bcl-2/Bcl-XL, thereby blocking the precursor effect of BAD apoptosis. [49][50][51] Furthermore, the 14-3-3 protein can bind to the apoptosis-regulating protein BAX of the Bcl-2 family, which prevents BAX from entering the mitochondria and thus terminating the regulatory effect of BAX on apoptosis.…”
Section: Figurementioning
confidence: 99%
“…Testicular germ cells and Sertoli cells have been shown to express the 14-3-3 theta isoform [41]. Apoptosis of rat testicular germ cells, induced by experimental varicocele, is controlled by 14-3-3 epsilon which regulates Bax and Bcl-2 expression in vitro [42].…”
Section: The 14-3-3 In Testesmentioning
confidence: 99%